Clinical relevance of algometric assessment of enthesitis using maastricht ankylosing spondylitis enthesitis index (MASES) in ankylosing spondylitis - Kaya, A.; Ozgocmen, S. (B M J Publishing Group, 2006)
[Abstract Not Available]
Annual European Congress of Rheumatology (EULAR 2006) -- JUN 21-24, 2006 -- Amsterdam, NETHERLANDS